Transdisciplinary perspectives on sharenting: parenting, privacy, and consent - Ferenc Lendvai, Gergely; Vizcaíno-Verdú, Arantxa; Velicu, Anca; Koltay, András (Routledge, 2026)
This book explores sharenting—the widespread practice of parents or caregivers sharing information about their children online—and explores how this pervasive digital practice is reshaping childhood, parenting, and family life in a networked society. Offering a transdisciplinary framework that integrates legal, sociological, psychological, and communication-based perspectives, the book examines sharenting from the micro-level of family life to the societal macro-level. It conceptualizes sharenting simultaneously as a communicative practice, a mode of identity construction, an evolving set of family rituals, a source of intergenerational conflict, and a regulatory challenge, among other dimensions. It also addresses emerging dynamics such as influencer parenting, datafication, children’s vulnerability as data subjects, and the growing risks associated with technologies that enable synthetic media, including deepfakes. With contributors from Central-Eastern Europe, the Baltic States, Türkiye, and the Global South alongside Western scholars, the volume provides a rare comparative view of the interaction between global platforms and locally situated forms of parenting and governance. The book will appeal to scholars and students interested in parenting in the digital world from a range of disciplines: sociology, media studies, psychology, law, socio-legal studies, communication studies, childhood and youth studies, and family studies.
Keywords: behavioral sciences; communication studies; computer science; development studies; education; health and social care; humanities; law; social sciences; social work; urban studies; environment